2014
DOI: 10.1021/mp500646d
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose Respiratory Recombinant Adenovirus-Based Vaccine Provides Long-Term Protection for Non-Human Primates from Lethal Ebola Infection

Abstract: As the Ebola outbreak in West Africa continues and cases appear in the United States and other countries, the need for long-lasting vaccines to preserve global health is imminent. Here, we evaluate the long-term efficacy of a respiratory and sublingual (SL) adenovirus-based vaccine in non-human primates in two phases. In the first, a single respiratory dose of 1.4 × 109 infectious virus particles (ivp)/kg of Ad-CAGoptZGP induced strong Ebola glycoprotein (GP) specific CD8+ and CD4+ T cell responses and Ebola G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 56 publications
(107 reference statements)
0
33
0
Order By: Relevance
“…However, at the same time point in that study, complete protection against EBOV (Kikwit strain) was observed in animals that received the ChAd3-EBOV-SUDV vaccine prime followed by an MVA-EBOV-SUDV boost. A small study that used a recombinant Ad5 (rAd5) codon-optimized EBOV vaccine, delivered by the respiratory route, showed protection against homologous EBOV (Kikwit strain) challenge 21 weeks after the final vaccination, suggesting that durability may be improved by respiratory, rather than intramuscular, administration of this vaccine 266 . The rVSV-MARV vaccine completely protected cynomolgus monkeys against homologous MARV (Musoke strain) challenge if the animals were challenged 14 months after the single-injection vaccination 267 .…”
Section: Box 2 | Vaccination To Prevent Filovirus Infectionmentioning
confidence: 99%
“…However, at the same time point in that study, complete protection against EBOV (Kikwit strain) was observed in animals that received the ChAd3-EBOV-SUDV vaccine prime followed by an MVA-EBOV-SUDV boost. A small study that used a recombinant Ad5 (rAd5) codon-optimized EBOV vaccine, delivered by the respiratory route, showed protection against homologous EBOV (Kikwit strain) challenge 21 weeks after the final vaccination, suggesting that durability may be improved by respiratory, rather than intramuscular, administration of this vaccine 266 . The rVSV-MARV vaccine completely protected cynomolgus monkeys against homologous MARV (Musoke strain) challenge if the animals were challenged 14 months after the single-injection vaccination 267 .…”
Section: Box 2 | Vaccination To Prevent Filovirus Infectionmentioning
confidence: 99%
“…The development of an orally or intranasally administered Ad5-vectored EVD vaccine has been pursued [67,68], and a recent study suggests that sublingual administration of an adenovirus-based vaccine may provide durable protection at least in nonhuman primates [69]. Oral administration of a live adenovirus-vectored vaccine abrogates the relevance of pre-existing vector immunity, resulting in a robust immune response to the delivered antigen [42,43,70,71].…”
Section: Eplication-incompetent Vectored Vaccinesmentioning
confidence: 99%
“…Intranasal immunization with Ad5-vectored Zaire GP has been tested in guinea pigs [48] and macaques [49]. The macaque study also evaluated combined intranasal and intratracheal, or sublingual immunization.…”
Section: Pre-clinical Testing Of Adenovirus-vectored Ebola Vaccinesmentioning
confidence: 99%